Three-component spiropyran synthesis via tandem alkylation-condensation. Issue 23 (5th June 2020) - Swinson, Harriet; Perry, Alexis
Abstract: A catalyst-free, three-component alkylation-condensation cascade for spiropyran synthesis has been developed, using readily available building blocks (indoles, alkyl halides, salicylaldehydes) and environmentally benign solvents (water, ethanol). A cascade approach enables this sequence to proceed under mild conditions which, in turn, promote broad substrate tolerance and operational simplicity. Consequently, we have demonstrated the utility of this process in the synthesis of 25 structurally-diverse spiropyrans, incorporating useful functionality across the spiropyran framework, and on multi-gram scale. Graphical abstract: Image 1